STRATEGI BERTUTUR PEMBAWA ACARA PADA AKUN MEDIA SOSIAL YOUTUBE VINDES: KAJIAN PRAGMATIK - Marini Rehanisafira; Novia Juita (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
The background of this research is how the form of strategy or technique used in the host's speech on the VINDES youtube social media account regarding the issue of criticism of the government which is a topic of conversation on social media. The purpose of this study is based on the selected problems, namely: (1) to analyze the strategy of speaking frankly without further ado by the host on the VINDES youtube social media account with pragmatic studies; (2) to analyze the strategy of speaking frankly with the positive politeness of the host on VINDES's YouTube social media account with pragmatic studies; (3) to analyze the strategy of speaking with the host's negative politeness on the social media account YouTube VINDES with a pragmatic study; (4) to analyze the strategy of the host's vague speech on the VINDES youtube social media account with a pragmatic study; (5) for the strategy of speaking in the heart or being silent as the host on the VINDES YouTube social media account with pragmatic studies. Data collection techniques use observing techniques and note-taking techniques. The data used are the stories of Vincent and Desta in the VINDES program. Based on the results of data analysis, the strategy of speaking contained in the host's speech on the VINDES youtube channel is a strategy of speaking frankly without preamble, the strategy of speaking frankly with positive politeness, the strategy of speaking frankly with negative preamble, the strategy speak vaguely. The speech strategy that is most often found in the presenter's speech is the strategy of speaking without further ado and the strategy of speaking that is not on YouTube VINDES is the strategy of speaking in the heart or being silent.